Impaired cytotoxic function and exhausted phenotype of natural killer cells in VEXAS syndrome - Breillat, Paul; Carbone, Francesco; Lereclus, Emilie; Riller, Quentin; d'Izarny-Gargas, Thibaut; Possémé, Céline; Templé, Marie; Zhao, Lin-Pierre; Luka, Marine; Lazaro, Estibaliz; Outh, Rodereau; Le Guenno, Guillaume; et al. (Blood, 2025)
-NK cell phenotyping reveals impaired cytotoxicity, chronic activation, and exhaustion in VEXAS syndrome.-Decreased circulating NK cells were independently associated with an increased risk of severe infections in VEXAS syndrome. VEXAS (vacuoles, E1 enzyme, X-linked, autoinflammatory, somatic) syndrome is an autoinflammatory disorder caused by acquired somatic UBA1 mutations in hematopoietic stem cells, affecting peripheral myeloid and natural killer (NK) cells. Given the high rate of severe infections observed in VEXAS patients, we hypothesized that NK cell dysfunction contributes to this increased susceptibility. We conducted a comprehensive immune characterization of peripheral NK cells in patients with VEXAS (n=40), patients with autoinflammatory diseases without UBA1 mutations (n=22), and elderly gender-matched healthy controls (HCs) (n=16). Multiparameter phenotyping was performed using CyTOF, scRNAseq, whole-blood stimulation assays and in vitro NK cell cytotoxic assay. Peripheral NK cells in VEXAS were quantitatively and qualitatively impaired. Mass cytometry revealed reduced frequencies of mature cytotoxic CD56dim NK cells and an expansion of the CD56high CD16dim subset. NK cells exhibited features of exhaustion, including increased PD-1 expression, and reduced levels of cytotoxic markers such as NKp46 and CD8α. scRNAseq analysis showed decreased signatures of cytotoxicity and IL-2 and IFN-γ production, alongside increased inflammatory signatures. Whole blood stimulation assays confirmed impaired IL-2, IFN-γ, and granzyme B production following TLR3, TLR4, and TLR7/TLR8 agonist stimulation. Extended NK phenotyping by flow cytometry confirmed reduced activating receptors’ expression and impaired IFN-γ production in VEXAS. Moreover, in vitro UBA1 inhibitors impaired NK cell cytotoxic capacity and promote cell death. Finally, reduced NK cell frequencies were independently associated with an increased risk of severe infections. These findings suggest that NK cell dysfunction in VEXAS syndrome contributes to increased susceptibility to severe infections.